2021
DOI: 10.1159/000513724
|View full text |Cite
|
Sign up to set email alerts
|

Topical Applications of a Heparinoid-Containing Product Attenuate Glucocorticoid-Induced Alterations in Epidermal Permeability Barrier in Mice

Abstract: Introduction: Either systemic or topical glucocorticoids (GCs) can cause significant adverse effects on cutaneous structure and function. Although some products and ingredients can improve GC-induced abnormalities in epidermal permeability barrier, the efficacy is moderate. Prior studies in normal mice showed that topical applications of a heparinoid-containing product, Hirudoid® cream, improve epidermal barrier function by upregulation of epidermal proliferation, expression of mRNA for epidermal differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In our previous report [31], MPS increased the protein levels of claudin-1 and ZO-1, a TJ constituent, in normal HEKa. Wen et al [32] reported that topical MPS-containing products increased mRNA expressions of epidermal differentiation markers and lipid synthetic enzymes in clobetasol propionate-containing product-induced skin barrier impairment in mice. Indeed, the abnormal cell morphology of keratinocytes induced by CP also tended to normalize after 72 h of coadministration of 1 μg/mL MPS (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous report [31], MPS increased the protein levels of claudin-1 and ZO-1, a TJ constituent, in normal HEKa. Wen et al [32] reported that topical MPS-containing products increased mRNA expressions of epidermal differentiation markers and lipid synthetic enzymes in clobetasol propionate-containing product-induced skin barrier impairment in mice. Indeed, the abnormal cell morphology of keratinocytes induced by CP also tended to normalize after 72 h of coadministration of 1 μg/mL MPS (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of hyaluronic acid with its receptor CD44 has also been reported to inhibit CP-induced skin atrophy [29], and in the CD44 knockout keratinocytes, claudin-1 expression is reduced and TJ barrier formation is delayed [37]. Recently, it has been reported that MPS-containing creams suppress CP-induced skin atrophy in mice and show efficacy against CP-induced impairment of the epidermal permeability barrier [32] and that treatment of keratinocytes with MPS increases TJ-related proteins such as claudin-1 and ZO-1 [31]. In consideration of these reports, it is suggested that CD44 activation may be involved in the increased expression of TJ-related proteins in MPS, but the relationship with CD44 signaling needs to be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, MPS cream might improve the appearance of acne scars by promoting epidermal proliferation and improving epidermal barrier function. Topical heparinoids raised the levels of mRNA expression in mouse skin for proteins involved in epidermal differentiation (filaggrin and involucrin), lipid synthesis (HMGCoA and SPT1), and epidermal proliferation 30,31 . In addition to the respective effects of the two treatments themselves, part of the reason for the superior efficacy of the combined therapy may be that the laser promoted drug delivery via the skin, which enhanced the penetration and absorption of MPS cream so that it could better exert its effects 32 …”
Section: Discussionmentioning
confidence: 99%
“…It not only elevated the expression levels of epidermal mRNA for lipid production, such as HMGCoA, fatty acid synthase (FAS), and serine palmitoyltransferase 1 (SPT1), but also increased the expression levels of some skin proteins, including filaggrin, involucrin, and loricrin (37,38). Furthermore, when combined with TCS, MPS cream could largely prevent TCS-induced elevation in TEWL in comparison to TCS alone (39), which was also consistent with the result of this meta-analysis (21). Second, MPS cream also showed some anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%